The drive of digital literacy skills in the 21st century / Farina Tazijan, Rofiza Aboo Bakar and Nor Fazlin Mohd Ramli - Tazijan, Farina; Aboo Bakar, Rofiza; Mohd Ramli, Nor Fazlin (Universiti Teknologi MARA, Pulau Pinang, 2022)
With the advent of technology, the internet is the main source often to millions of answers. By clicking one button, it answers many questions one might have. However, the certainty of what is right or wrong, true or false is ambiguous. Literacy in the 21st century is about constructing and validating knowledge. The more information there is, the more readers have to know how to navigate through ambiguity and triangulate and validate viewpoints. As such, learning in a digital world has become more challenging today. With the mass media content, information on the internet contributes to the misinformation itself, fake news, information bias, or even truthfulness of the posted information. Hence, acquiring digital skills in this era is essential for internet users, particularly students who make up the majority of the internet users. With the COVID-19 pandemic and school closures, students have to school from home on their own. This crisis may explain that it is urgent to develop autonomous and advanced digital skills to prepare students in the online learning environment. Educators and learners are becoming more dependent on the internet. Therefore, this paper proposes the needed skills in reading digitally for online students.